Hubungan Antara Self-Regulation dengan Kecenderungan Adiksi Game Online pada Mahasiswa Fakultas Teknologi Informasi Universitas Kristen Satya Wacana - Prasetiani, Aprilia Tri; Setianingrum, Margaretta Erna (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2020)
This study aims to investigate the relationship between self-regulation with a tendency to addiction to online games in the satyawacanachristian university faculty student information technology. The number of samples were 95 people. Methods of data collection in the from of online gaming addiction variable Game Addiction Scale, which was adopted from the theory of Griffths and Davies (2004) which describes the dependence on online game on to student based on DSM IV criteria by developing seven aspects including: Sailience, Tolerance, Mood Modification, Relapse, Withdrawal Symptoms, Conflict, and Problems. In the variable self-regulation using Self Regulation Quesionaire (SRQ) from Brown, Millier, and Lawendowski (1999).The results of this study showed the value of the product moment correlations rxy= -0.545 ; p = 0.00 (p < 0,05), which means there is a negative and significant relationships between self-regulation on the trend of online gaming addiction in satya wacana christian university information technology faculty students.